Education Across the Life Course - Hans-Peter Blossfeld (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
There is a huge demand for high-quality longitudinal educational research in Germany. In particular, there is a clear need for both analytical and methodological progress in order to understand educational pathways through the life course and how they lead to different outcomes. This paper identifies the theoretical and methodological challenges of studying education across the life course and describes the structure of the National Educational Panel Study (NEPS) in Germany.
Keywords: 330; competence development; educational decisions; formal; informal and non-formal educational environments; returns to education; educational trajectories; life course research; longitudinal analysis; panel data